Exploring the financial consequences of the servitization of manufacturing - Neely, Andrew (Springer Science Business Media, 2008)
Commentators suggest that to survive in developed economies manufacturing firms have to move up the value chain, innovating and creating ever more sophisticated products and services, so they do not have to compete on the basis of cost. While this strategy is proving increasingly popular with policy makers and academics there is limited empirical evidence to explore the extent to which it is being adopted in practice. And if so, what the impact of this servitization of manufacturing might be. This paper seeks to fill a gap in the literature by presenting empirical evidence on the range and extent of servitization. Data are drawn from the OSIRIS database on 10,028 firms incorporated in 25 different countries. The paper presents an analysis of these data which suggests that: [i] manufacturing firms in developed economies are adopting a range of servitization strategies—12 separate approaches to servitization are identified; [ii] these 12 categories can be used to extend the traditional three options for servitization—product oriented Product–Service Systems, use oriented Product–Service Systems and result oriented Product–Service Systems, by adding two new categories “integration oriented Product–Service Systems” and “service oriented Product–Service Systems”; [iii] while the manufacturing firms that have servitized are larger than traditional manufacturing firms in terms of sales revenues, at the aggregate level they also generate lower profits as a % of sales; [iv] these findings are moderated by firm size (measured in terms of numbers of employees). In smaller firms servitization appears to pay off while in larger firms it proves more problematic; and [v] there are some hidden risks associated with servitization—the sample contains a greater proportion of bankrupt servitized firms
Keywords: Manufacturing; Service; Servitization; Product–service systems; Value added; Globalisation; International comparison